A Review of the Cuban Health System Policlinico - Marzilli, Colleen (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
It is fascinating to evaluate the health system of Cuba. In a time when the world as a whole is struggling with how to meet health needs and improve health outcomes around the globe, lessons can be learned from each country. Cuba presents a unique perspective related to meeting the health needs of its people, and through this review of the policlinico, these are discussed.